A Sociolinguistic Analysis of Adress Terms in the Movie Matilda (1996) - Nurazizah Yova Ekaputri; Nakhwa Nabilla Atmaja; Lenni Herawati Sirait; Balqis Azwar Lubis; Rahmadsyah Rangkuti (Journal on Education, 2025)
The objective of this research was to analyze the types of address terms used in the movie Matilda (1996). This study employed a descriptive qualitative approach. Researchers observed the film, identified relevant timestamps, and analyzed the function of each address term within its context to gather data. The data was then analyzed using Wardhaugh's (2010) theory. The findings revealed several types of address terms: 7 instances of first names (FN) including Michael, Matilda, Amanda, Jen, Bob, Bill, and Zinnia; 3 instances of title and last names (TLN) in Miss Trunchbull, Mr. Wormwood, and Miss Honey; 1 instance of a title (T) in Sir; 2 instances of last names (LN) in The Wormwoods and The Trunchbull; 7 instances of pet names (PN) such as Dearest pie, Lovekins, My Heartstrings, Snickerdoodle, Honeydew, and Little Brucey; and 5 instances of kinship terms (KT) such as Mom, Mommy, My boy, and Daddy. Based on the results, it can be concluded that first name (FN) were the most commonly used address terms, with intimacy being the primary reason for their usage with the total of 28 address term found.